Tentative epidemiologic cut-off value and resistant characteristic detection of apramycin against Escherichia coli from chickens. Issue 16 (13th September 2019) - Tian, Erjie; Muhammad, Ishfaq; Hu, Wanjun; Wu, Zhiyong; Li, Rui; Lu, Xiaoxiao; Chen, Chunli; Li, Jichang
ABSTRACT: Escherichia coli are important foodborne zoonotic pathogens. Apramycin is a key aminoglycoside antibiotic used by veterinarians against E. coli . This study was conducted to establish the epidemiological cut-off value (ECV) and resistant characteristics of apramycin against E. coli . In this study, 1412 clinical isolates of E. coli from chickens in China were characterized. Minimum inhibitory concentrations (MICs) of apramycin were assessed by broth microdilution method. MIC50 and MIC90 for apramycin against E. coli (0.5–256 µg/mL) were 8 and 16 µg/mL, respectively. In this study, the tentative ECV was determined to be 16 µg/mL by the statistical method and 32 µg/mL by ECOFFinder software. Besides, the percentages of aac(3)-IV positive strains ascended with the increase of MIC values of apramycin, and the gene npmA was detected in strains with higher MICs. Sixteen apramycin highly resistant strains displayed multiple drug resistance (100%) to amoxicillin, ampicillin, gentamicin, doxycycline, tetracycline, trimethoprim and florfenicol, while most of them were susceptible to amikacin and spectinomycin. In summary, the tentative ECV of apramycin against E. coli was recommended to be 16 µg/mL. Abstract : The tentative ECV of apramycin against E. coli was determined to be 16 µg/mL, and the aac(3)-IV gene was found to be MIC dependent.